A STUDY OF SPEAKING PROBLEMS ENCOUNTERED BY NURSING DEPARTMENT STUDENTS AT UNIVERSITAS SUMATERA BARAT - Warni, Asis; Jufry, Allen Christy (Ensiklopedia Research and Community Service Review, 2024)
The study is intended to figure out the problems of speaking encountered by Nursing Department students at “Universitas Sumatera Barat”. In conducting the research, the researchers used descriptive method.Total sampling technique was employed as the methodology in gaining the sample.The data of the research was collected by using speaking test in the form of interview. The result of the research shown  that the most to the least problems of speaking encountered by the Nursing students of “Universitas Sumatera Barat” as the followings; the first position is comprehension about thirteen students or 50%.The second, vocabulary around 38,4% or ten students. The third, fluency 34,9% or nine students.The fourth position is grammatical problems, consists of eight students or 30,7%. The last position is pronunciation, they are seven students or 26,9 % of sample students get problem on pronunciation.Keywords: Speaking, Speaking-Problems, Nursing Students